چاندنی کەلتوری لەسەردەمی تۆڕە کۆمەڵایەتییەکاندا - حسن, ئاشتی حمە صالح حسێن (Sulaimani Journal for Humanities, 2023)
The theory of cultural cultivation is one of the theories that has received constant attention from the media and the researchers in this field, since the beginning of the development of visual media, (the theory of cultural cultivation) predicted the impact of visual media on cultural cultivation compared to other educational centres, from the perspective of the assumptions of the theory of cultural cultivation. The importance of this study lies in the fact that it examines the possibility of the role of social networks as an alternative to traditional media in cultural cultivation from the perspective of cultural cultivation theory. In this study called (cultural cultivation, in the era of social networks), the researcher tried to reach a conclusion about the main objective of the research, which is: exploring the impact of social networks on the process of (cultural cultivation) among Kurdish users (students of the University of Sulaymaniyah), and she also tried to answer the main question of the research, which is: (What is the extent of the impact of the intensity of exposure to the use of social networks on (cultural cultivation) among users who are university students (study sample)?, For this purpose, the researcher followed the descriptive approach, and relies on one of the data collection tools, which is the creation of a questionnaire consisting of (22) scientific questions (excluding defining questions). All questions were directed to the study sample of students who used social networks and were students from the University of Sulaymaniyah / Department of media / for the academic year 2022-2023. Finally, the study reached several important conclusions, including: - When the study sample use social networks "frequently" and "intensively", it greatly affects the cultural formation of the users in all areas of life, - this proves that the process of cultural cultivation through social networks is much more effective than other common media, especially Television, upon which (the theory of cultivation) is based. - Social networks are primarily more influential on (cultural cultivation) among Kurdish consumers/university students (study sample), compared to other traditional media, including television.
Keywords: Keywords cultural cultivation social networking sites